USING LASER PHOTODYNAMIC THERAPY IN THE TREATMENT OF AUTOIMMUNE THYROIDITIS - Sadikhov, F.G. (World of Medicine and Biology, 2023)
The purpose of the study was to comparatively assess the effectiveness of treating patients with a diffuse form of autoimmune thyroiditis using laser photodynamic therapy and traditional treatment. The work was based on examination and treatment data of 90 patients in whom the concentrations of a number of hormones were examined: TSH, FT3, FT4, and Anti-TPO. In each group, the relative values of the analyzed indices, their mean error (m), and the reliability of intergroup differences (according to the χ² criterion) were calculated. Conservative therapy in patients of the control group brought a positive result only in 32 (64 %) patients, while in 18 patients out of 50 (36 %), signs of subclinical hypothyroidism, as well as structural changes in the thyroid gland, persisted in later dates (≥21 days). In the main group, hormone levels clearly improved, approaching normal values, indicating the absence of hypothyroidism signs in this group.
Keywords: autoimmune thyroiditis; photodynamic therapy; photoditazine